RT001 in Progressive Supranuclear Palsy-Clinical and In-Vitro Observations - Plamena R. Angelova; Kristin M. Andruska; Mark G. Midei; Mario Barilani; Paldeep Atwal; Oliver Tucher; Peter Milner; Frederic Heerinckx; Mikhail S. Shchepinov (MDPI AG, 2021)
Progressive supranuclear palsy (PSP) is a progressive movement disorder associated with lipid peroxidation and intracerebral accumulation of tau. RT001 is a deuterium reinforced isotopologue of linoleic acid that prevents lipid peroxidation (LPO) through the kinetic isotope effect. The effects of RT001 pre-treatment on various oxidative and bioenergetic parameters were evaluated in mesenchymal stem cells (MSC) derived from patients with PSP compared to controls. In parallel, 3 patients with PSP were treated with RT001 and followed clinically. MSCs derived from PSP patients had a significantly higher rate of LPO (161.8 ± 8.2% of control; p < 0.001). A 72-h incubation with RT001 restored the PSP MSCs to normal levels. Mitochondrial reactive oxygen species (ROS) overproduction in PSP-MSCs significantly decreased the level of GSH compared to control MSCs (to 56% and 47% of control; p < 0.05). Incubation with RT001 significantly increased level of GSH in PSP MSCs. The level of mitochondrial DNA in the cells was significantly lower in PSP-MSCs (67.5%), compared to control MSCs. Changes in mitochondrial membrane potential, size, and shape were also observed. Three subjects with possible or probable PSP were treated with RT001 for a mean duration of 26 months. The slope of the PSPRS changed from the historical decline of 0.91 points/month to a mean decline of 0.16 points/month (+/−0.23 SEM). The UPDRS slope changed from an expected increase of 0.95 points/month to an average increase in score of 0.28 points/month (+/−0.41 SEM). MSCs derived from patients with PSP have elevated basal levels of LPO, ROS, and mitochondrial dysfunction. These findings are reversed after incubation with RT001. In PSP patients, the progression of disease may be reduced by treatment with RT001.